2021
DOI: 10.1002/ccr3.5025
|View full text |Cite
|
Sign up to set email alerts
|

Sudden bilateral hearing loss after vestibular‐evoked myogenic potentials

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Preclinical work based on different animal models has demonstrated that, depending upon the noise characteristics, noise overexposure often leads to cellular damage in the peripheral vestibular system with a well-characterized effect on the response of otolith organs [ 28 , 29 , 30 , 31 ]. Studies using vestibular evoked myogenic potentials (VEMPs) [ 31 , 32 , 33 , 34 ] have provided evidence of the same in individuals with NIHL and in military veterans. Latency shifts, reductions in VEMP amplitudes, increased VEMP thresholds, and absent VEMPs have been shown in NIHL populations with abnormalities correlated to both hearing thresholds and history of noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical work based on different animal models has demonstrated that, depending upon the noise characteristics, noise overexposure often leads to cellular damage in the peripheral vestibular system with a well-characterized effect on the response of otolith organs [ 28 , 29 , 30 , 31 ]. Studies using vestibular evoked myogenic potentials (VEMPs) [ 31 , 32 , 33 , 34 ] have provided evidence of the same in individuals with NIHL and in military veterans. Latency shifts, reductions in VEMP amplitudes, increased VEMP thresholds, and absent VEMPs have been shown in NIHL populations with abnormalities correlated to both hearing thresholds and history of noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by using body-conducted (BC) stimuli throughout. The incentive to use BC stimuli followed from consideration of safe sound (Mattingly et al, 2015;Asakura & Kamogashira, 2021), raising concerns about the very high air-conducted (AC) stimulus levels required to evoke a VEMP response.…”
Section: Introductionmentioning
confidence: 99%
“…This is a critical aspect in AC VEMP testing, considering the potential cochlear detrimental effect of cumulative repeated loud AC stimuli commonly needed in VEMP (7,8). Anecdotical cases of bilateral hearing loss due to AC VEMP (9,10) have been reported and precautional sound exposure levels have been released (11,12).…”
Section: Introductionmentioning
confidence: 99%